Lamellar ichthyosis: a case report - Özyürek, Hamit; Kavak, Ayşe; Alper, Murat (The Turkish Journal of Pediatrics, 2002)
Ichthyoses are divided into four groups according to clinical, histopathologic and genetic findings. Lamellar ichthyosis is one of them. The incidence of lamellar ichthyosis is believed to be approximately 1 per 100,000 to 300,000 live births. It is characterized by large, polygonal, grayish brown, and tightly adherent scales. We report a four-year-old boy with desquamative lesions since birth who had six-year-old sister with similar lesions, suggesting an autosomal recessive inheritance. His skin biopsy revealed hyperkeratosis with lamellae. There were no associated hair or neurological abnormalities. His clinical and histopathological findings were typical for isolated lamellar ichthyosis. Because of its rare occurrence, we report this case with a review of the literature.